Identification of a First Human Norovirus CD8+ T Cell Epitope Restricted to HLA-A*0201 Allele - Malm, Maria; Vesikari, Timo; Blazevic, Vesna (Frontiers in Immunology, 2018)
Norovirus (NoV) causes a substantial global burden of acute gastroenteritis in all age groups and the development of NoV vaccine is a high priority. There are still gaps in understanding of protective NoV-specific immunity. Antibody mediated immune responses have been widely studied, but in contrast, the research on NoV-specific human T cell-mediated immunity is very limited. We have recently reported NoV capsid VP1-specific 18-mer peptide (134SPSQVTMFPHIIVDVRQL151) to induce strong CD8+ T cell immune responses in healthy adult donors. This work extends to identify the precise NoV T cell epitope and the restricting human leucocyte antigen (HLA). Pentamer technology was used to detect HLA-A*0201-restricted T cell-mediated responses to 10-mer peptide 139TMFPHIIVDV148 of four healthy adult blood donors. Immunogenicity of the 10-mer epitope was confirmed by ELISPOT IFN-g and intracellular cytokine staining (ICS) on flow cytometry. A population of CD3+CD8+ T lymphocytes binding to HLA-A*0201/TMFPHIIVDV pentamers was identified in two HLA-A*0201-positive donors. Recognition of the 10-mer epitope by T cells resulted in a strong IFN-g secretion as shown by ELISPOT assay. In addition, ICS confirmed that high proportion (31% and 59%) of the TMFPHIIVDV epitope-specific CD3+CD8+ T cells in the two donors had multifunctional phenotype, simultaneously producing IFN-g+ IL-2 and TNF-a cytokines. In the present study novel human NoV HLA-A*0201-restricted minimal 10-mer epitope 139TMFPHIIVDV148 in the capsid VP1 was identified. The HLA-peptide pentamer staining of T cells from healthy donor PBMCs and cytokine responses in ex-vivo ELISPOT and ICS assays suggest that this epitope is recognized during NoV infection and activates memory phenotype of the epitope-specific multifunctional CD8+ T cells. The importance of this epitope in protection from NoV infection remains to be determined.